(untitled) (AYUSHDHARA, 2024)
Amavata is an Ama pradoshaja vikara, caused by Agnimandya, which leads to accumulation of Ama in Shleshmasthana and Prakopa of Vata dosha, resulting in pain, stiffness and swelling of joints, which closely resembles the chronic inflammatory autoimmune disorder called Rheumatoid arthritis. Prevalence of rheumatoid arthritis is approximately 0.8% worldwide and 0.5-0.75% in India. Materials and Methods: A 44 years female presented with pain in multiple joints associated with swelling and stiffness since 2 years was diagnosed as Amavata. The patient was treated with Kottamachukkadi lepa, Dashamoola kashaya and Dhanyamla Kayaseka, Vaitarana basti followed by Guduchyadi kashaya basti along with Rasayana and oral medications. Results: There was a significant improvement in overall symptoms. Conclusion: Contemporary medicine offers DMARDS and steroid medications for very long time as it is Auto immune condition. Whereas on other hand Panchakarma therapies can target on root cause of the Vyadhi and provide more promising results.